Empowering Farmers through Vermicomposting: Shahina Begum's Journey from a Homemaker to an Entrepreneur - Sadaf, Bushra Humaira; Haque, Abdul; Miajy, Abdullah; Ahmed, Sharif; Bhandari, Humnath (CGIAR System Organization, 2024)
In the small rural village of Khamergragram in Kishoreganj, Nilphamari Shahina Begum, once a full-time homemaker, has transformed her life through sustainable farming practices. With only 13 decimals of land, she runs a thriving household-based farm, contributing to her family’s livelihood and environmental health. Her journey started two years ago when she became involved in the CGIAR Initiative on Sustainable Intensification of Mixed Farming Systems (SI-MFS), a global project funded by the Consortium of International Agricultural Research Centers (CGIAR), operating in six countries, including Bangladesh.